Hydrothermal treatment and iodine binding provide insights into the organization of glucan chains within the semi‐crystalline lamellae of corn starch granules. Issue 8 (27th May 2014) - Vamadevan, Varatharajan; Hoover, Ratnajothi; Bertoft, Eric; Seetharaman, Koushik
ABSTRACT: The importance of glucan chains that pass through both the amorphous and crystalline lamellae (tie chains) in the organization of corn starch granules was studied using heat‐moisture treatment (HMT), annealing (ANN), and iodine binding. Molecular structural analysis showed that hylon starches (HV, HVII, and HVIII) contained higher proportion of intermediate glucan chains (HVIII > HVII > HV) than normal corn (CN) starch. Wide angle X‐ray scattering revealed that on HMT, the extent of polymorphic transition in hylon starches decreased with increasing proportion of intermediate and long chains. Iodine treated hylon starches exhibited increased order in the V‐type polymorphism as evidenced by the intense peak at 20° 2θ and the strong reflection intensity at 7.5° 2θ and the extent of the change depended on the type of hylon starch. DSC results showed that the gelatinization enthalpy of CN and waxy corn starch (CW) remained unchanged after ANN. However, hylon starches showed a significant increase in enthalpy with more distinct endotherms after ANN. It can be concluded that tie chains influence the organization of crystalline lamellae in amylose extender mutant starches. © 2014 Wiley Periodicals, Inc. Biopolymers 101: 871–885, 2014.